(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Corpus linguistics has revolutionized the study of languages, offering empirical insights into linguistic patterns, usage, and evolution. This article explores the methodologies and applications of corpus linguistics as a powerful tool for understanding linguistic phenomena. It highlights its role in lexicography, language teaching, sociolinguistics, and discourse analysis, emphasizing its potential to bridge theory and practice in language research.